Intracellular papillae of Actinocephalus (Eriocaulaceae-Poales) roots and their interaction with fungi: A light and transmission electron microscopy study - Oriani, Aline; Scatena, Vera L. (Elsevier B.V., 2007)
The genus Actinocephalus comprises 25 species and is restricted to Brazil, occurring mainly in the Espinhaco Mountains of Minas Gerais and Bahia States. Previous anatomical studies have reported the occurrence of intracellular papillae in the Actinocephalus roots, without dealing with their ultrastructure and function. The purpose of this paper is to investigate the structure, the composition and the probable function of the intracellular papillae of Actinocephalus roots, based on light microscopy, transmission electron microscopy and histochemical tests. The intracellular papillae occurred in all root tissues, from the rhizodermis to the vascular cylinder; they presented different forms and sizes and, ultrastructurally, they corresponded to material deposited between the cell wall and the plasma membrane. The histochemical tests carried out were positive for cellulose, pectin and callose. The intracellular papillae are responses of the plant cells to the interaction with fungi. They work as a physical barrier restricting fungal penetration, and they may also favor the supply of water and nutrients to the plant, since they increase root absorption surface. This might explain why the species of Actinocephalus are among the tallest Eriocaulaceae despite their reduced radicular system and the nutritional deficiency of the soil in which they grow. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Actinocephalus; Eriocaulaceae; Poales; intracellular papillae; Anatomy; Ultrastructure; Fungi